Circadian rhythms and photoperiodism in insects - Stehlík, Jan (Jihočeská univerzita, 2008)
In this thesis we present experimental data and discuss circadian rhythm regulation in the housefly, Musca domestica. Our findings suggest that, although differences in the mechanisms of circadian rhythm regulation between Musca domestica and Drosophila melanogaster are not as fundamental as was originally expected, they still provide interesting insight into the evolution of biological clocks. We also studied possible involvement of one of the circadian clock genes, timeless, in photoperiodic induction of diapause in a drosophilid fly, Chymomyza costata. We found the transcription of tim gene to be strongly disrupted in CNS of npd-mutant (non-photoperiodic-diapause) larvae. Analysis of genomic structure of tim gene revealed that the promoter of timelessnpd allele carries a large deletion, a possible cause of disruption of photoperiodic calendar function in npd-mutant larvae of C. costata.
Circadian rhythms and photoperiodism in insects
Keywords: circadian clocks; photoperiodism; Musca; Chymomyza; circadian rhythms; circadian clocks; photoperiodism; Musca; Chymomyza; circadian rhythms